Managing Mangrove Resources in Conflict of Interest Zones in Bangka Island's Eastern Coast - Bidayani, Endang; Vieira, Lucas O.; Valen, Fitri Sil (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
The east coast of Bangka Island is an area prone to conflicts of interest, due to the use of the coast for tin mining and fishing by traditional fishermen. The threat of destruction of mangrove forests due to community tin mining on the east coast of Bangka Island has caused a decline in the crab population as the main catch of local fishermen.The study aimed to analyze efforts to manage mangrove ecosystems in conflict zones. The study was conducted from June to October 2023. The primary data was obtained through interviews fishermen community, direct observation, and documentation. The data analysis methods employed utilize a descriptive approach.  Based on the survey results, the impact of tin mining activities causes a decrease in the area of mangrove forests. Reporting that the income of traditional fishermen in the productive fishing season is around IDR 65,000/day or IDR 980,000/month. Meanwhile, in the bad season, the income of traditional fishermen is IDR 13,000/day or IDR 205,000/month.  Efforts to manage mangrove resources in conflict zones include mangrove restoration and mangrove forest educational tourism. The government's enforcement of regulations regarding the prohibition of tin mining in mangrove forest areas must be more massive so that mangrove resources remain sustainable. The government must significantly enhance the enforcement of legislation pertaining to the prohibition of tin mining in mangrove forest regions in order to ensure the long-term sustainability of mangrove resources.